2017
DOI: 10.1074/jbc.m117.781492
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear insulin-like growth factor 1 receptor phosphorylates proliferating cell nuclear antigen and rescues stalled replication forks after DNA damage

Abstract: We have previously shown that the insulin-like growth factor 1 receptor (IGF-1R) translocates to the cell nucleus, where it binds to enhancer-like regions and increases gene transcription. Further studies have demonstrated that nuclear IGF-1R (nIGF-1R) physically and functionally interacts with some nuclear proteins, the lymphoid enhancer-binding factor 1 (Lef1), histone H3, and Brahma-related gene-1 proteins. In this study, we identified the proliferating cell nuclear antigen (PCNA) as a nIGF-1R-binding partn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 52 publications
0
30
0
Order By: Relevance
“…Several different mechanisms for the involvement of IGF1R in radioresistance have been proposed. Nuclear IGF1R is known to physically interact with and phosphorylate proliferating cell nuclear antigen (PCNA), a key mediator of the DNA damage response (Waraky et al ., ). A role for IGF1R has been suggested in both of the major pathways for repairing DNA double‐strand breaks, namely homologous recombination and non‐homologous end joining (Chitnis et al ., ).…”
Section: Role Of Igf System In Chemoresistancementioning
confidence: 97%
“…Several different mechanisms for the involvement of IGF1R in radioresistance have been proposed. Nuclear IGF1R is known to physically interact with and phosphorylate proliferating cell nuclear antigen (PCNA), a key mediator of the DNA damage response (Waraky et al ., ). A role for IGF1R has been suggested in both of the major pathways for repairing DNA double‐strand breaks, namely homologous recombination and non‐homologous end joining (Chitnis et al ., ).…”
Section: Role Of Igf System In Chemoresistancementioning
confidence: 97%
“…They further showed that translocation to the nucleus was mediated by SUMOylation of IGF-1R by the SUMO modifier SUMO-1. It has since been shown that nuclear IGF-1R interacts with several different nuclear proteins and functions to regulate the cell cycle, DNA damage responses, invasion, and metastasis (26)(27)(28)(29).…”
Section: Intracellular Igf-1r Insr and Hybrid-rmentioning
confidence: 99%
“…Mass spectrometry analyses identified 13 phosphorylation sites on PCNA, of which Y211 and S261 seem to be most prevalent [ 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 ] ( Figure 7 and Supplementary Table S1 ). Phosphorylation of PCNA on Y211 by the epidermal growth factor receptor (EGFR) enhances the stability of chromatin-bound PCNA but also weakens its interaction with mismatch repair proteins and thus suppresses the mismatch repair pathway [ 134 , 135 ] ( Figure 8 ).…”
Section: Post-translational Modifications Of Proliferating Cell Numentioning
confidence: 99%
“…Phosphorylation of PCNA on Y211 by the epidermal growth factor receptor (EGFR) enhances the stability of chromatin-bound PCNA but also weakens its interaction with mismatch repair proteins and thus suppresses the mismatch repair pathway [ 134 , 135 ] ( Figure 8 ). Furthermore, a crosstalk between phosphorylation and ubiquitination seems to be important for replication stress response in light of the recent findings that phosphorylation of Y60, Y133 and Y250 by IGF-1R promotes PCNA ubiquitination and replication fork restart after UV or MMS exposure [ 131 ].…”
Section: Post-translational Modifications Of Proliferating Cell Numentioning
confidence: 99%
See 1 more Smart Citation